Frequency of Urinary Tract Infection Among Patients withUtero-Vaginal Prolapse - Ahmad, Nadia; Khattak, Sania Tanweer; Khanam, Faiza; Ayub, Asma (Indus Journal of Bioscience Research, 2025)
Background: Utero-vaginal prolapse is a frequent pelvic floor disorder in women especially in middle and older age groups. The condition can disturb normal bladder position and urine flow which may increase the risk of urinary tract infection. Local data regarding this problem is limited particularly from Swat region. Objective: To determine the frequency of urinary tract infection among patients with utero-vaginal prolapse. Study Design: Cross sectional study. Duration and Place of Study: This study was carried out from 1st September 2024 to 1st March 2025 in the Department of Obstetrics and Gynecology Saidu Group of Teaching Hospital Swat. Methodology: A total of 178 women aged 18 to 60 years diagnosed with utero-vaginal prolapse were included. Urinary tract infection was defined by fever above 38°C along with pyuria and positive culture. Data were analyzed using Statistical Package for Social Sciences version 25. Chi square test and Fisher exact test were applied, with p ≤ 0.05 considered significant. Results: The mean age was 46.82 ± 6.85 years. Urinary tract infection was found in 27 patients, giving a frequency of 15.20%. No statistically significant association was observed between urinary tract infection and age, body mass index, duration of symptoms, comorbidities, residence or degree of prolapse (p > 0.05). Conclusion: Urinary tract infection is a common complication among patients with utero-vaginal prolapse.